IMPLEMENTATION OF STANDARD OPERATING PROCEDURES OF SMK3 IN THE PROCESSED RICE INDUSTRY OF CV MITRA BERKAH IN PAROMPONG, WEST BANDUNG REGENCY. - Paulus Sukapto; Marihot Nainggolan; Sani Susanto; Sugih S Tjandra (Ann Publisher, 2026)
Abstract Background. Currently, public knowledge, particularly regarding the Occupational Safety and Health Management System (SMK3), remains limited. In fact, if the understanding of SMK3 is good, the number of work accidents is getting less, work productivity is getting higher, and finally, the number of products produced is increasing, with the quality also getting better. Purpose. The purpose of implementing the PKM program is to increase the understanding, knowledge, and insight of CV Mitra Berkah Parompong, West Bandung Regency, as an industry player about POB SMK3. Method. In this program, location surveys, interviews before and after the seminar were conducted. The training and mentoring material is an explanation of SMK3, the application of SMK3 in instant rice processing. Conclusion. After participating in this mentoring, it is hoped that they will gain a deeper understanding of the POB of SMK3 and apply it correctly and adequately in the community.